Design optimization of integrated cooling inserts in modular Fischer-Tropsch reactors. (15th March 2023) - Barrera, Jorge L.; Hartvigsen, Joseph J.; Hollist, Michele; Pike, Jenna; Yarosh, Ainsley; Fullilove, Nicholas P.; Beck, Victor A.
Highlights: Fischer–Tropsch reactor with cooling inserts for improved thermal management. Systematic design approach finds the layout of highly conductive cooling inserts. Optimal fin geometry maximizes reactor productivity while avoiding thermal runaway. Computer-driven topology optimization automates and accelerates the design process. Abstract: Sustainable production of liquid fuels and feedstocks from atmospheric CO2 through carbon recycling technologies is necessary to broaden decarbonization efforts and further reduce global emissions. Fischer–Tropsch (FT) reactors can address this challenge by providing storable, high-value liquid hydrocarbon fuels and feedstocks from syngas generated through reductive CO2 utilization. FT technology, however, is most cost effective at large-scale, fixed-site plants and does not effectively address the smaller, globally distributed CO2 point sources. Alternatively, smaller, modular reactors can be composed together to the specific scale of the emission source, yielding a flexible solution that enables more widespread deployment. In these modular reactors, thermal management using a finned cooling insert embedded within the catalyst matrix is critical to maintaining the performance and viability. Thus, in this work, topology optimization is used to determine the cooling insert geometry that maximizes reactor productivity while preventing auto-thermal runaway. Optimal designs are generated for varying number of constituent fins and over a range of maximum operating temperatures. Constraints including minimum feature length-scales and prescribed cooling insert material are imposed on the designs to enhance manufacturability. The impact of design features such as insert tapering and increased length scale hierarchy is automatically revealed by the systematic design framework employed. This approach thus generates novel optimal geometries while automating, accelerating, and enhancing the design process compared to traditional heuristic approaches for cooling insert design in modular FT reactors.